The Dominant Errors of Speech Production Committed in Speaking Class Interaction - Akhadiyatus Sholihah Ts (State Institute for Islamic Studies IAIN of Metro, 2019)
This study describes the dominant errors committed by the first and third-semester students of the English Education Department of UII. The aim of this research is to describe the dominant errors committed by the first and third-semester students of UII. This is a qualitative research study. The researcher collects the data through an audio recording, listens and makes the script from the audio recording, read the script and identifies the data, selects the data, and classifies the silent pause of error and filled the pause. The researcher analyses the data uses the theory of Clark and Clark and Dulay. The result indicates that the total errors are 84 utterances containing 108 silent pauses for the first semester and 32 Utterances containing 34 silent pauses for the third semester, and 51 utterances containing 57 filled pauses for the first-semester student and 89 utterances containing 124 filled pauses for the third semester students. Silent pause is the dominant errors made by the first semester students and filled pause is the dominant errors made by the third semester student. The error sources are cognitive reason and situational anxiety.